Pembelajaran Pendidikan Kewarganegaraan berbasis portofolio - Dasim Budimansyah (Jurnal Civics: Media Kajian Kewarganegaraan, 2006)
The conduct of civic teaching up to now still faces some barriers and limitations so its mission to make good citizen is not yet being realized in value-based education corridor. Based this reality, it is imperative to conduct a comprehension study on basic problems so the civic education can be empowered as a poweifu1 learning area characterized by contextual learning experience such as meaningful, integrated, value-based, challenging, and activating. Through these kinds of learning experiences, student be facilitated in constructing democratic civic knowledge, attitude, and skills in constructive psycho-pedagogic corridor.